Size-Controlled Synthesis of Cobalt Phosphide co2p Nanoparticles and Their Application in Non-Enzymatic Glucose Sensors Via a Carbon Fiber/Co2p Composite - Ruiz-Leon, D; Ruiz-Leon, D (Elsevier B.V., 2024)
In this study, we synthesized Co2P nanoparticles using a solid-state phosphorization method and evaluated the electrocatalytic response to glucose oxidation reaction (GORs). The influence of synthesis conditions on the particle size, morphology of Co2P species and formation of byproducts is discussed. A lower molar ratio of the phosphorus precursor leads to a decrease in the generation of byproducts. In addition, the calcination temperature and time greatly influence the purity level of the Co2P species and its particle size. Thus, we obtained three pure Co2P nanoparticles with different sizes and morphologies. Significant differences in their electrocatalytic activity against the GOR are observed depending on the size of the particles, being the smaller ones the most efficient. Based on Tafel analysis, a higher catalytic activity was observed for the carbon fibre (CF)/Co2P composite compared to Co2P, which presented a greater onset potential and low response in current density. Tafel slopes close to 120 mV/dec were obtained for both materials, indicating that the mechanism is independent of the type of Co2P-based material used. Finally, the performance of the GCE/CF/Co2P sensor was demonstrated by amperometric measurements, with a sensitivity of 409 µAmM-1cm-2, a linear range between 39.4 µM and 150 µM, and a detection limit of 0.97 µM, analytical characteristics better than those obtained for other cobalt phosphide-based sensors reported in the literature. In addition, the GCE/CF/Co2P sensor shows excellent selectivity and demonstrated to be competitive compared to other Co-based non-enzymatic glucose sensors. © 2024